Prediction of water inflow after excavation of underground chamber group with long span and high buried depth - Rui LI; Hongfu ZHOU; Shuwu LI; Guanghong JU; Wanlin LIU; Wenqing TANG (Shuiwen dizhi gongcheng dizhi)
Predict the water inflow after excavation of large underground caverns is crucial for the safe construction and operation of underground engineering. To predict the water inflow of underground caverns after excavation and provide guidance for drainage and anti-seepage design, this study focused on the large underground powerhouse caverns of a pumped storage power station in Xinjiang, and analyzed the seepage characteristics of rock mass in the dam site area in terms of groundwater activity characteristics, borehole water pressure test, and the development of structural planes in the rock mass. To enhance the reliability of the prediction results, the change of groundwater seepage field and normal water inflow after excavation of underground caverns are analyzed and predicted by groundwater dynamics method and numerical analysis method, respectively. The results show that significant seepage and drainage occur after the excavation of the underground caverns, with the main powerhouse bearing the majority of the water inflow from the surrounding cavern group. The most prone to seepage failure and deformation is located at the corner of the excavation line of the cavern. The normal water inflow after excavation of the cavern group predicted by the groundwater dynamics method and the numerical analysis method are 7 442.88 m3/d and 7 218.32 m3/d, respectively, resulting in a 3.1% error, demonstrating strong agreement between the two methods. Based on engineering safety considerations, the calculation result of Sato’s empirical formula 7 442.88 m3/d is selected as the predicted value of normal water inflow after excavation of underground powerhouse cavern group of a pumped storage power station. These findings provide a scientific basis for the drainage and anti-seepage design of a large underground cavern group in the early stage of construction.